Gereja dan Hak Anak Berkebutuhan Khusus: Studi Kualitatif tentang Sekolah Minggu di Jemaat GKE Galilea Palangka Raya - Binti, Alexandra; Selpie, Selpie; cambah, Tahan (Jurnal Teologi Pambelum, 2025)
This study explores the understanding and role of the church in serving persons with disabilities, focusing on the Sunday School for Children with Special Needs (SHM ABK) at the Galilea congregation of the Evangelical Church in Kalimantan (GKE) Palangka Raya. While Sunday School is a common ministry within GKE, a dedicated program for children with special needs remains relatively new. According to Samuel Kabue and Arne Fritzson, the church should be a community for all, and Rob van Kessel emphasizes that a vital church involves every member without exception. Employing a qualitative method through observation and interviews, this research investigates the congregation’s understanding and the church’s role in SHM ABK. Data were analyzed by integrating scholarly perspectives with field findings. The study reveals theological ambiguities among congregants, reflected in liturgy and worship practices, which hinder the effectiveness of ministry to children with special needs. These ambiguities also indicate broader limitations in other church ministries. The study argues that the church must be a fellowship inclusive of all members, and that full participation—including of children with special needs—is essential to sustaining the vitality of its ministry.